The Role of Digital Technologies in Online Learning: A Study on the Students' Perceptions - Fachrunnisa, Nurul; Tanasy, Novalia; Nuraeni, Nuraeni (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2023)
This research aims to find out the role of digital technologies in online learning based on the students’ perceptions. The qualitative descriptive method is applied in this research. The researchers implied semi-structured interview to collect the data with 10 English Education Department students of Maros Muslim University as the participants. The interviews are done by individually and recorded through audio recording. The findings of this research show two different perceptions from students. The first, students who think that online learning using digital technology is very helpful to assist them in understanding the material well because they can directly look for on the internet and they can repeat the materials many times in learning platform. The second, students who argue that utilizing digital technology in online learning is not effective since the direct interaction is absence. They feel difficult to communicate with the teachers in virtual way when the teaching and learning process is run so that they cannot comprehend the material well. Likewise, some students are bothered with the unstable internet network that makes them are difficult to attend the online learning smoothly. Therefore, all of these perceptions can lead to the positives and negatives of the usage of digital technologies in online learning. Keywords: Digital technologies, online learning, students’ perceptions